Drivers of transactional sexual relationships among students in a Nigerian University: implications for elimination of reproductive rights violation - Ige, Oluwatosin Sunday; Solanke, Bola Lukman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the study was to assess the prevalence and drivers of transactional sex in a Nigerian University. Methods: Data was collected through Mobile Data Collection platform (Google form). The dependent variable was transactional sex. The independent variables are self-reported household wealth group, gender, current age, marital status, age at sexual debut, family structure, consumption of alcohol, and use of psychoactive drugs. Two binary logistic regression models were fitted. Results: The prevalence of transactional sex was 23.85%. The odds of transactional sex were higher among females (OR=1.642, 95% CI: 1.499-1.799) and older students, but lower among undergraduates who were 18 years or older at the time of first intercourse (OR=0.842, 95% CI: 0.764-0.927). Results further revealed that while being from richest household wealth group (OR=0.587, 95% CI: 0.486-0.710) and being from a nuclear family structure (OR=0.446, 95% CI: 0.213-0.933) lowers the odds of transactional sex, the use of psychoactive drugs and alcoholic consumption increased the likelihood of transactional sex among undergraduates. Conclusions: The drivers of transactional sex in tertiary institutions in Nigeria are age, age at sexual debut, family structure, use of psychoactive drugs and alcoholic consumption. Promoting responsible sexual behaviour of undergraduates is imperative in the country.